Notice of Retraction Performance Investigation of Coaxial Cable with Transmission Line Parameters Based on Lossy Dielectric Medium - Gebremedhn Wubet Wagaye (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeecs.iaes@gmail.com.-----------------------------------------------------------------------This paper presents the analysis of high performance for coaxial cable with transmission line parameters. The modeling for performance of coaxial cable contains many parameters, in this paper will discuss the more effective parameter is the type of dielectric mediums. This analysis of the performance related to dielectric mediums with respect to dielectric losses and its effect upon cable properties, dielectrics versus characteristic impedance, and the attenuation in the coaxial line for different dielectrics. The analysis depends on a simple mathematical model for coaxial cables to test the influence of the insulators (Dielectrics) performance.